Implementasi Metode Fast Fourier Transform pada Sistem Monitoring Voltage Flicker - Rani Kurnia; Riki Mukhaiyar (Dinasti Research, 2021)
West Sumatra is recorded to have an electrification ratio of 92.96%. Every year this figure will continue to increase, with the increase in the electrification ratio in West Sumatra, the quality of the required electric power will increase. Meanwhile, an increase in the electrification ratio will cause a decrease in the quality of electric power. The power quality of the electric power system is affected by disturbances. In other words, some disturbances occur in the electric power system which causes a decrease in power quality. The disturbance is in the form of external factors and internal factors. External factors include lightning, fallen trees, and others, while internal factors include short interruptions, voltage swells, voltage and current transients, and voltage flicker. Of these disturbances, the discussion will be focused on voltage flicker disturbances. Voltage flickers have several pathways, including causing malfunctions in the protective relay, and voltage surges that can cause bright and dim flickering of lighting lamps. The purpose of this final project is to create a tool to detect the presence of Voltage Flicker using the fast Fourier transform method so that it can observe the flicker that occurs with fast Fourier transform waves in Matlab applications.